¿Hay ecos de la sabiduría personificada en el “Cristo sabiduría de Dios” de 1 Cor 1, 18-31? (2020)
This study explores the possible relationship between personified Wisdom and the Christ-Wisdom of God in 1Co 1,24-30. The Greek and Jewish wisdoms are presented as context for Paul’s writing, starting with the wisdom in the Old Testament, the figure of the personified wisdom, followed by the wisdom in the New Testament, and the relationship between personified wisdom and Jesus Christ. Later, the paper analyzes 1 Co 1-4 as the center of gravity for the noun σοφία in all of the New Testament, and as the frame of reference to understand the pericope 1 Co 1,18-31. Finally, the paper identifies the echoes between the personified wisdom and the original Christ-Wisdom of God in 1 Co 1,24.30.